When Should We Stop Scanning Older Patients with Vestibular Schwannomas? - Borsetto, Daniele; Gair, Juliette; Kenyon, Olivia; Das, Tilak; Donnelly, Neil; Axon, Patrick; Macfarlane, Robert; Mannion, Richard; Scoffings, Daniel; Bance, Manohar; Tysome, James (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective Observation is a well-accepted management for small- to medium-sized vestibular schwannomas (VSs). Although there are good data on the natural history of this disease within adults, no studies have looked specifically at those aged over 70 years. Thus, there is a need for a surveillance protocol to determine if and when we can stop imaging safely patients aged 70 years and over with a new diagnosis of VSs when managed with observation.Design Over a 13-year period, we retrospectively analyzed all skull base unit patients with a sporadic unilateral VSs managed with an imaging surveillance protocol. All data were collected prospectively with a minimum follow-up of 5 years.Setting Tertiary referral skull base unitParticipants Patients aged 70 years and over with sporadic VSs at diagnosisMain Outcome Measures Main outcome measuresResults A total of 112 patients met inclusion criteria. The median age at diagnosis was 74 years (range: 70–87 years). The mean follow-up was 82 months (range: 60–144). The size of the VSs at diagnosis was intracanalicular (IC) in 46%, small in 41%, medium in 12%, and large in 2%.Growth was more likely where tumors were extracanalicular (EC) rather than IC at presentation (p = 0.036) and within the first 18 months after diagnosis (p < 0.001). Twenty-nine percent of VSs displayed growth (6% continued surveillance, 23% received active treatment). Good hearing at diagnosis did not predict tumor stability for IC or EC tumors (p = 0.162 and p = 0.536).Conclusions Since no VSs grew after 42 months from diagnosis, our data support an initial magnetic resonance imaging (MRI) at 6 months after diagnosis followed by an annual MRI for 3 years. At this point, consideration could be given to discussing discontinuation or further imaging with patients.
Keywords: vestibular schwannoma; acoustic neuroma; surveillance; observation; elderly